Complete Response of Synchronous Liver Metastasis in a Pancreatic Ductal Adenocarcinoma, When Surgery Could Represent a Therapeutic Option - Antonella Argentiero; Angela Calabrese; Angela Monica Sciacovelli; Sabina Delcuratolo; Antonio Giovanni Solimando; Oronzo Brunetti (Canadian Journal of Gastroenterology and Hepatology)
Metastatic pancreatic ductal adenocarcinoma (PDAC) is characterized by poor prognosis and short survival. Today, the use of new polytherapeutic regimens increases clinical outcome of these patients opening new clinical scenario. A crucial issue related to the actual improvement achieved with these new regimens is represented by the occasional possibility to observe a radiological complete response of metastatic lesions in patients with synchronous primary tumor. What could be the best therapeutic management of these patients? Could surgery represent an indication? Herein, we reported a case of a patient with PDAC of the head with multiple liver metastases, who underwent first-line chemotherapy with mFOLFIRINOX. After 10 cycles, he achieved a complete radiological response of liver metastases and a partial response of pancreatic lesion. A duodenocephalopancreasectomy was performed. Due to liver a lung metastases after 8 months from surgery, a second-line therapy was started with a disease-free survival and overall survival of 8 months and 45 months, respectively. Improvement in the molecular characterization of PDAC could help in the selection of patients suitable for multimodal treatments. This trial is registered with NCT02892305 and NCT00855634.